2021
DOI: 10.3390/ph14101045
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Is a Mild Carrier-Dependent Uncoupler of Oxidative Phosphorylation and a Modulator of Mitochondrial Permeability Transition

Abstract: Pioglitazone (PIO) is an insulin-sensitizing antidiabetic drug, which normalizes glucose and lipid metabolism but may provoke heart and liver failure and chronic kidney diseases. Both therapeutic and adverse effects of PIO can be accomplished through mitochondrial targets. Here, we explored the capability of PIO to modulate the mitochondrial membrane potential (ΔΨm) and the permeability transition pore (mPTP) opening in different models in vitro. ΔΨm was measured using tetraphenylphosphonium and the fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Upregulation of ferritin, the iron-storage form, can limit the availability of iron in the body and thus limit ferroptosis (Ma et al, 2022). Another GPX4-independent pathway revealed by our analysis is the interaction of PGZ with CDGSH iron-sulphur domain-containing protein 1 (mitoNEET), an outer mitochondrial membrane protein that plays a crucial role in mitochondrial iron homeostasis (Kharechkina et al, 2021). MitoNEET is reportedly a mitochondrial PGZ target and has been shown to be overexpressed in various compartments, including the heart (Kharechkina et al, 2021;Yuan et al, 2016).…”
Section: Crosstalk Between Pgz and Mitochondrial Functionsmentioning
confidence: 75%
See 1 more Smart Citation
“…Upregulation of ferritin, the iron-storage form, can limit the availability of iron in the body and thus limit ferroptosis (Ma et al, 2022). Another GPX4-independent pathway revealed by our analysis is the interaction of PGZ with CDGSH iron-sulphur domain-containing protein 1 (mitoNEET), an outer mitochondrial membrane protein that plays a crucial role in mitochondrial iron homeostasis (Kharechkina et al, 2021). MitoNEET is reportedly a mitochondrial PGZ target and has been shown to be overexpressed in various compartments, including the heart (Kharechkina et al, 2021;Yuan et al, 2016).…”
Section: Crosstalk Between Pgz and Mitochondrial Functionsmentioning
confidence: 75%
“…The uncoupling properties of ANTs are reported to be secondary to their intrinsic ability to mediate H + leakage across the inner mitochondrial membrane, which leads to mitochondrial membrane potential disruption, proton gradient dissipation and eventually mitochondrial uncoupling (Demine et al, 2019). The ability of PGZ to induce ANT-mediated uncoupling was also suggested in a recent study performed with isolated rat liver mitochondria (Kharechkina et al, 2021) as the study revealed that the coadministration of carboxyatractyloside (an ANT inhibitor) with PGZ-containing medium ameliorated PGZ-induced mitochondrial depolarisation and uncoupling activities, suggesting that the latter effects were mediated by ANTs (Kharechkina et al, 2021).…”
Section: Crosstalk Between Pgz and Mitochondrial Functionsmentioning
confidence: 94%
“…86 Hence, the beneficial pleiotropic activities of TZDs, and in particular TZD efficacy in controlling T2D glycaemia, may indicate benefit in spite of, rather than due to PPARg activation, 87 thereby implying a TZD target beyond PPARg. 83 Indeed, similar to metformin, TZDs are reported to inhibit mitochondrial complex I, [88][89][90][91] resulting in AMPK activation, 92 and suppression of mTORC1 kinase activity. [93][94][95][96][97][98] Thus, the suppression of hyperactive mTORC1 by TZDs may account for their apparent insulin-sensitising activity, resulting in glycaemic control while suppressing insulin secretion.…”
Section: Pparg Activation By Tzds Results In Transcriptional Activati...mentioning
confidence: 99%
“…Indeed, similar to metformin, TZDs are reported to inhibit mitochondrial complex I, 88–91 resulting in AMPK activation, 92 and suppression of mTORC1 kinase activity 93–98 . Thus, the suppression of hyperactive mTORC1 by TZDs may account for their apparent insulin‐sensitising activity, resulting in glycaemic control while suppressing insulin secretion.…”
Section: Type 2 Diabetes Standard‐of‐care Treatments Suppress Hyperac...mentioning
confidence: 99%
“…For solidified SNEDDS, the slower release of PGZ from S-SNEDDS as compared to L-SNEDDS counterparts was attributed to the physical interaction of L-SNEDDS carrying the drug with the hydrophobic structures of silica particles within the adsorbent powder [46,47]. Upon adsorption, the lipid formulation becomes trapped in the intraparticular pores of the adsorbent particles and causes a reduction in the dissolution rate [48]. However, the difference in the release profiles among the different S-SNEDDS formulations was attributed to the structural differences among the four utilized silica powders; specific surface area of the powder controls the dissolution process and formulation release is higher with a larger surface area.…”
Section: Discussionmentioning
confidence: 99%